Abnormal Returns in Privatization Public Offerings: The Case of Portuguese Firms - Carla Vieira; Ana Paula Serra (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper provides evidence on abnormal returns of Portuguese privatization public offerings for the period from 1989 to 2001. Previous empirical studies report the existence of underpricing for privatized firms in the short-run and positive abnormal returns in the long run. This study explores the abnormal performance of a comprehensive sample of Portuguese privatization transactions and investigates the determinants of the observed price behavior. Our results are not supportive of the underpricing phenomenon except if we exclude the very extreme observations. The results show further that privatization IPOs underperform private sector IPOs. In the long run, we observe negative abnormal returns. While in early event months, privatization public offerings yield more negative returns than private sector offerings, this effect is reversed in longer horizon periods. Initial underpricing is thus reversed and investors seem to require higher returns in partial privatizations.
Keywords: G38; G32; 330; Privatization; IPOs; Privatisierung; Wertpapieremission; Portugal